THE SECTORAL FINANCING DIVERSIFICATION AND THE PROFITABILITY OF ISLAMIC BANKING IN INDONESIA - Widarjono, Agus; Sidiq, Sahabudin Sidiq (Jurnal Ekonomi dan Bisnis Islam (Journal of Islamic Economics and Business), 2022)
This study investigates the influence of sectoral financing concentration on the profitability of Islamic banking in Indonesia. The data is aggregated by Indonesian Islamic banks from January 2015 to June 2021. Islamic banks are divided into two, namely Islamic commercial banks and Islamic window banks. The study used Autoregressive distributed lag (ARDL) and Panel Mean Group (PMG). The results showed that sectoral financing concentration increased the profitability of Islamic commercial banks while diversification of sectoral financing boosted the profitability of Islamic window banks. In addition, this study also showed that size and inefficiency negatively affected the profitability of Islamic commercial banks and window banks. This result implies that the right sectoral financing policy for Islamic commercial banks is financing concentration. This strategy implies that Islamic commercial banks must build competitiveness in certain sectors of the economy. For this reason, there is a need to increase the skills of the worker to build a competitive advantage in the sector that is the focus of financing. In comparison, sectoral financing diversification is more applicable for Islamic window banks. To support this diversification strategy, banks must conduct good supervision in the financing, especially sectoral financing based on profit-sharing contracts.